Equity, Diversity, and Canadian Labour - Korinek, Valerie J. (Labour / Le Travail, 2009)
The article reviews the book, "Equity, Diversity, and Canadian Labour," edited by Gerald Hunt and David Rayside.
Keywords: BOOKS -- Reviews; EQUITY, Diversity & Canadian Labour (Book); HUNT, Gerald; Labor; Nonfiction; RAYSIDE, David